Effect of intramuscular midazolam premedication on patient satisfaction in women undergoing general anaesthesia: a randomised control trial - Kwang Ho Lee; Seung Woo Song; Younghyun Jin; Hyunjae Lim; Jonghoon Lee (BMJ Open)
Objective To determine the effect of premedication with intramuscular midazolam on patient satisfaction in women undergoing general anaesthesia.Trial design, setting and participants Double-blind, parallel randomised control trial at a tertiary care medical centre in South Korea. Initially, 140 women aged 20–65 years who underwent general anaesthesia and had an American Society of Anesthesiology physical status classification of I or II were randomly assigned to the intervention group or the control group, and 134 patients (intervention n=65; control n=69) completed the study.Intervention Intramuscular administration of midazolam (0.05 mg/kg) or placebo (normal saline 0.01 mL/kg) on arrival at the preoperative holding area.Main outcomes The primary outcome was the patient’s overall satisfaction with the anaesthesia experience as determined by questionnaire responses on the day after surgery. Satisfaction was defined as a response of 3 or 4 on a five-point scale (0–4). The secondary outcomes included blood pressure, heart rate, oxygen desaturation, recovery duration and postoperative pain.Results Patients who received midazolam were more satisfied than those who received placebo (percentage difference: 21.0%, OR 3.56, 95% CI 1.46 to 8.70). A subgroup analysis revealed that this difference was greater in patients with anxiety, defined as those whose Amsterdam Preoperative Anxiety and Information Scale anxiety score was ≥11, than that for the whole sample population (percentage difference: 24.0%, OR 4.33, 95% CI 1.25 to 14.96). Both groups had similar heart rates, blood pressure and oxygen desaturation.Conclusion Intramuscular administration of midazolam in women before general anaesthesia in the preoperative holding area improved self-reported satisfaction with the anaesthesia experience, with an acceptable safety profile.Trial registration number KCT0006002.